Platelet RNA modules point to coronary calcification in asymptomatic women with former preeclampsia. (December 2019) - Hartman, Robin J.G.; Korporaal, Suzanne J.A.; Mokry, Michal; de Jager, Saskia C.A.; Meeuwsen, John A.L.; van der Laan, Sander W.; Lansu, Nico R.; Zoet, Gerbrand A.; Pasterkamp, Gerard; Urbanus, Rolf T.; Hoefer, Imo E.; Franx, Arie; et al.
Abstract: Background and aims: Women who develop preeclampsia during pregnancy are at a higher risk for developing cardiovascular disease. As platelets are affected by preeclampsia, we set out to identify whether platelets carry information in their transcriptome on cardiovascular risk in women with former preeclampsia. Methods: Platelets were isolated from asymptomatic women with previous preeclampsia, who underwent screening with coronary computed tomography angiography. Platelet RNA was isolated and used to construct gene networks using an unbiased approach. Platelet gene modules assembled from the network were related to risk factors and clinical traits of these women, including coronary artery calcium scores (CACS). Results: We found multiple gene modules which correlated with CACS (correlation coefficients: 0.44 to 0.59, p = 0.05 to 0.007). The genes from two clinically relevant modules were expressed at a higher level in the group with calcifications ( p = 3.9 × 10 −10 and 0.02) and enriched for platelet-related gene-sets such as platelet activation. The first of these modules was also enriched ( p permutation = 0.0546) for genes mapped to known coronary artery disease susceptibility loci. Additional unbiased network analyses in platelet RNA of patients with overt cardiovascular disease underlined the importance of the identified modules for disease by high preservation. ( p = 1.6 × 10 −9 to 1.7 × 10 −47 ). Conclusions: We found platelet RNA modules that correlated with CACS in asymptomatic women with previous preeclampsia. Whether or not platelets directly contribute to this disease trajectory, or reflect the underlying plaque substrate remains to be determined, but enrichment for coronary artery disease susceptibility genes emphasizes the importance for the disease. Graphical abstract: Image 1 Highlights: Network construction shows transcript modules in platelet RNA. Modules associate with calcification in asymptomatic women with former preeclampsia. Platelet activation and coagulation pathways are enriched in the calcification modules. Relevant modules are enriched for coronary artery disease susceptibility loci. Platelet RNA gene modules may be useful to detect abnormalities in the circulation.